Sprachliche Situation in der Europäischen Union - Zhetpisbajeva, B.A.; Tleuzhanova, G.K.; Mikhailova, N.B. (KSU Publ., 2011)
Different language situations in the European Union countries, peculiarities of social language evolution, and modern problems of communication in the varied world are given in this article; the status and meaning of each separate language are defined. The languages are as a means of academician, professional mobility achievement, as an instrument of multilingual and successful integration in the society. The reference of European educational politics in the sphere of language is given by authors, directed to the increasing of mutual understanding of all Europe citizens, increasing quality and quantity level of European collaboration.
Еуропалық Одақ мемлекеттеріндегі тіл жағдайы
Keywords: language; European; understanding; mobility; education; politics; multilingual; career development; European cooperation